Dynamic Preference for NADP/H Cofactor Binding/Release in E. coli YqhD Oxidoreductase - Rajni Verma; Jonathan M. Ellis; Katie R. Mitchell-Koch (Molecules, 2021)
YqhD, an E. coli alcohol/aldehyde oxidoreductase, is an enzyme able to produce valuable bio-renewable fuels and fine chemicals from a broad range of starting materials. Herein, we report the first computational solution-phase structure-dynamics analysis of YqhD, shedding light on the effect of oxidized and reduced NADP/H cofactor binding on the conformational dynamics of the biocatalyst using molecular dynamics (MD) simulations. The cofactor oxidation states mainly influence the interdomain cleft region conformations of the YqhD monomers, involved in intricate cofactor binding and release. The ensemble of NADPH-bound monomers has a narrower average interdomain space resulting in more hydrogen bonds and rigid cofactor binding. NADP-bound YqhD fluctuates between open and closed conformations, while it was observed that NADPH-bound YqhD had slower opening/closing dynamics of the cofactor-binding cleft. In the light of enzyme kinetics and structural data, simulation findings have led us to postulate that the frequently sampled open conformation of the cofactor binding cleft with NADP leads to the more facile release of NADP while increased closed conformation sampling during NADPH binding enhances cofactor binding affinity and the aldehyde reductase activity of the enzyme.